1992
DOI: 10.1136/jech.46.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the frequency of "severe" accidental injury in childhood.

Abstract: Study Objective-The aim was to improve the epidemiological information concerning child accidental injuries which can be extracted from routine inpatient and coroners' inquest data.Design-This was a retrospective study of coroners' inquest reports and inpatient case notes to undertake objective severity scaling and to extract basic data. This material was related to denominators from OPCS midyear population estimates, to 1981 census ward populations, and to sociodemographic data collected in a local census in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 16 publications
0
27
1
1
Order By: Relevance
“…Available morbidity data typically consist of Accident and Emergency department attendance records, but often with little information about severity. Given that minor injuries may have different risk factors from the severe ones of interest to health policy makers (Stewart-Brown et al 1986, Walsh andJarvis 1992), these data may be of little use. Other data sets, such as Road Traffic Accident reports from STATS19 are also likely to be of limited use in isolation, given systematic threats to their comprehensiveness (Cryer et al 1995).…”
Section: Injury Reduction: the Evidence Basementioning
confidence: 99%
“…Available morbidity data typically consist of Accident and Emergency department attendance records, but often with little information about severity. Given that minor injuries may have different risk factors from the severe ones of interest to health policy makers (Stewart-Brown et al 1986, Walsh andJarvis 1992), these data may be of little use. Other data sets, such as Road Traffic Accident reports from STATS19 are also likely to be of limited use in isolation, given systematic threats to their comprehensiveness (Cryer et al 1995).…”
Section: Injury Reduction: the Evidence Basementioning
confidence: 99%
“…Whether because of inadequate clinical information in the record or insufficient budgets for clerical transcription, in sorne provinces fewer than half of all injury separations are coded by external cause (58). Hospital separation data must also be generalized with caution because the decision to admit an injured child is often influenced by a variety of other factors such as patient age, bed availability, and social class (65,66).…”
Section: Limitations Of Routinely Collected National Datamentioning
confidence: 99%
“…There is conflicting evidence about socioeconomic gradients in injury morbidity in childhood. Some studies measuring use of health services have found higher rates of injury among children living in disadvantaged areas,39 but others have failed to find an association 1014. However, factors other than injury occurrence are likely to influence use of health services, such as proximity to hospital, 10 12 admission policies, and deprivation.…”
Section: Introductionmentioning
confidence: 99%